Auditing and assurances services : an integrated approach - Arens, Alvin A. (Hoboken, NJ : Pearson, 2023)
'Auditing and Assurance Services examines the process of conducting an audit from start to finish. The text's primary objective is to illustrate auditing concepts using practical examples and real-world settings. Using key real audit decisions as their foundation, students will be able to successfully conduct an audit according to a financial reporting framework'--
Includes index.
Buku bacaan asas prasiswazah Fakulti Ekonomi Pengurusan 2023/24.
Keywords: Auditing